Study of Self-Compassion, Depression, Anxiety and Stress in male and female teachers in Government College of Delhi and Uttar Pradesh in India - Tanwar, Kamini C.; Garg, Megha (International Journal of Psychosocial Rehabilitation, 2020)
The profession of teaching is considered as most prestigious among all. Learning either at school level or college level provides a good platform in development and success of an individual; teachers and faculties are the main pillar behind that success. The present research focuses on psychological aspect [self-compassion; depression, anxiety and stress (DAS)] of faculties in colleges and aims to (1) To find out the difference between male and female faculties on following variables: self-compassion; depression, anxiety and stress (DAS); (2) To find out relationship between self-compassion and DAS in male and female college teachers. The data was collected on 102 teachers from government colleges in Delhi and Meerut city in India through purposive sampling. The mean age range of the sample was 41.24 years. Data was collected with the help of Depression Anxiety and Stress (DAS) Scale (Lovibond and Lovibond , 1995) and Self Compassion Scale (Neff, 2003a). The results indicate that (1) there is no significant difference between male and female faculties on any variable, (2) there is a positive significant relationship among depression, anxiety and stress whereas no relationship between self-compassion and DAS in male college teachers. On the other hand, negative significant correlation between self-compassion and depression (-0.387, at .05 level) and positive significant relationship among depression, anxiety and stress in female college teachers was found.